Gambaran Kondisi Fisik Rumah Dan Hubungannya Dengan Resiko Penularan Tbc (Tuberkulosis) Di Kelurahan Kandang Mas Kota Bengkulu Tahun 2024 - Prayetno, Sigit; Yusmidiarti, Yusmidiarti (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Introduction: Tuberculosis (TB) is a contagious disease that remains a public health problem in Indonesia, especially in densely populated areas with substandard environmental health conditions.Research Objective: This study aims to describe the physical condition of the homes of TB patients in Kandang Mas Subdistrict, Bengkulu City, in 2024.Materials and Methods: This research uses a descriptive-analytic method with an epidemiological survey approach. Data were collected through direct observation of 28 homes of TB patients, with observed variables including ventilation rate, lighting, humidity, and room temperatureResearch Results: The results showed that the majority of homes did not meet the requirements in terms of ventilation rate (57.1%) and temperature (75%), while lighting (67.9%) and humidity (78.6%) generally met the standards.Conclusion: These findings indicate that inadequate air ventilation and non-ideal room temperature may contribute to an increased risk of TB transmission. Therefore, improving the physical condition of homes is an important step in the effort to prevent and control TB at the household level. Keywords: Tuberculosis; physical condition of the house; ventilation; temperature; lighting; humidity